Dietary patterns and inflammatory bowel disease: a global assessment of eight nutrients by region, gender, and socioeconomic status - He, Kun; Qin, YuChan; Li, BingBing; Ye, HongShi; Li, Cun; Qi, Kouyan; Jing, Nenglie; Yang, Yuping; Nie, Biao (Frontiers in Nutrition, 2025)
BackgroundThis study examines global intake patterns of eight dietary components associated with inflammatory bowel disease (IBD): fruits, non-starchy vegetables, processed meats, unprocessed red meats, saturated fats, monounsaturated fatty acids, omega-6 fatty acids, and dietary fiber. Consumption patterns were analyzed across demographic, geographic, and cultural dimensions, including region, sex, urban–rural residence, and educational level. This analysis reveals disparities in dietary intake and provides insights into the links between diet and IBD risk.MethodsThis study uses meta-analysis to evaluate the relationship between inflammatory bowel disease (IBD) and eight dietary components: fruit, non-starchy vegetables, processed meat, unprocessed red meat, dietary fiber, saturated fat, monounsaturated fatty acids, and omega-6 fatty acids. Drawing on data from the Global Dietary Database (GDD), a Bayesian model was employed to estimate intake levels and uncertainties at global and regional scales, incorporating variables such as education, urbanization, and the Socio-Demographic Index (SDI). The analysis covers global intake trends from 1990 to 2018 across 185 countries, and examines the association between educational attainment and IBD-related nutrient consumption from 1900 to 2015 in 145 countries. Instead of relying on traditional hypothesis testing, the study adopts uncertainty intervals (UIs), which provide probabilistic insights into dietary patterns and their variability across populations.ResultsBetween 1990 and 2018, processed meat intake showed the largest global increase among the eight dietary components, rising by 26% to 29.1 g/day (95% UI: 25.6–33.1). In Asia, unprocessed red meat intake rose by 38% to 53.5 g/day (95% UI: 42.1–67.6), and processed meat increased by 28% to 21.2 g/day (95% UI: 15.6–27.1). Non-starchy vegetable consumption in Central and Eastern Europe and Central Asia grew by 49%, reaching 182.8 g/day (95% UI: 146.2–228). In high-income countries, unprocessed red meat intake increased by 25% to 32.6 g/day (95% UI: 26.4–40.5). Latin America saw a 45% rise in vegetable intake, reaching 130.2 g/day (95% UI: 113.5–150.1), while the Middle East and North Africa reported a 13% increase to 152.1 g/day (95% UI: 129.8–177.4). South Asia experienced the most rapid relative growth in processed meat consumption (56%), reaching 4.6 g/day (95% UI: 2.4–8.2), although absolute intake remained low. In Sub-Saharan Africa, fruit consumption rose by 15%, to 81.5 g/day (95% UI: 71.3–93.5). These results reveal pronounced regional variation in dietary transitions over the past three decades, underscoring the importance of context-specific strategies to address changing dietary risk factors related to IBD.ConclusionThis study found that between 1990 and 2018, processed meat intake increased the most across 185 countries, rising by 26%, mirroring the global rise in IBD burden. The intake of eight dietary components showed significant heterogeneity across global populations, with variations by age, education level, and urbanization. These findings may inform policy interventions aimed at reducing intake in high-risk groups with high consumption of dietary factors linked to IBD, particularly in high-income countries and Asia, where IBD burden is increasing rapidly. The sharp rise in processed and unprocessed red meat intake, combined with long-term underconsumption of fruits, vegetables, and dietary fiber, likely contributes significantly to the rising IBD burden.